Small intestinal strangulation in a tear in the mesometrium of a nonpregnant mare. (11th May 2017) - Steward, S. K.; Bauck, A. G.; Zoll, W.; Conway, J. A.; Freeman, D. E.
Summary: Small intestinal strangulation was found at necropsy in the left mesometrium of a nonpregnant 10‐year‐old Quarter Horse mare subjected to euthanasia because of colic. The tear had smooth fibrotic edges, consistent with its development in one of two normal pregnancies, the last one at least 1 year preceding admission. This is a rare lesion and this report demonstrates that such a tear can develop during pregnancy without inducing small intestinal strangulation and that pregnancy is not required for strangulation to develop later. Therefore, all attempts should be made to close such tears at the time of initial surgery, if accessible, or later as a planned laparoscopic procedure.